Civitas dei, civitas diaboli. Temas y topoi en la literatura española - Vasas, László (Acta Hispanica, 2014)
The present article analyses some ofthe features that characterize the city as theme,especially regarding its expression in Spanishliterature. First of all, it focuses on the relationsbetween this theme and textuality, relevantobjectives of its configuration, properties alongwith literary proceedings. Next, it deals with themain topics of description, laudation andvituperation. Finally, two fragments appearingout of its plot context of the medieval Libro deAlexandre and the baroque El burlador de Sevillaare presented with an attempt of their justificationand interpretation.